Heidegger attuned to Bach. Thought and Affectivity in Being and Time - Sanò, Laura (Scenari, 2021)
“Being and Time can be considered as an immense Art of Fugue”. In these words Rachel Bespaloff formulates an opinion that explicitly links the work Heidegger published in 1927 with the great German composer’s unfinished masterpiece. Bespaloff’s interpretation of Being and Time is thus plotted chiefly along two coordinates: the musical “reading” of the work, seen as a grand “Art of Fugue”, and the strong stress on the notion of Befindlichkeit, taken as the essential feature of Dasein as thrownness. But the theoretical and hermeneutic apex of this approach to Heidegger’s work is the link it forges between these two aspects, i.e., its identification of “mood” as the foundation of music. This emerges from the fact that it is precisely in music that the two modes of disclosure – Verstehen and Befindlichkeit – fortify each other in their fullest manifestation.